2021
DOI: 10.1093/neuonc/noab129
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in association with stereotactic radiotherapy for non-small cell lung cancer brain metastases: results from a multicentric retrospective study on behalf of AIRO

Abstract: Background To define efficacy and toxicity of Immunotherapy (IT) with stereotactic radiotherapy (SRT) including radiosurgery (RS) or hypofractionated SRT (HFSRT) for brain metastases (BM) from Non-Small Cell Lung Cancer (NSCLC) in a multicentric retrospective study from AIRO (Italian Association of Radiotherapy and Clinical Oncology). Methods NSCLC patients with BM receiving SRT+IT and treated in 19 Italian centers were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Similarly, a multicentric retrospective study from AIRO (Italian Association of Radiotherapy and Clinical Oncology) for patients with brain metastases from NSCLC reported that patients with the interval between SBRT and IO ≤ 7 days had a longer survival compared with the interval between SBRT and IO > 7 days. 413 This study data supports the delivery of SBRT and IO within a short time frame given that concurrent therapy is shown to be more effective without having an impact on toxicity. In conclusion, these data from clinical trials and retrospective studies indicate that concurrent iRT may be more effective than sequential one.…”
Section: Clinical Practicesupporting
confidence: 70%
“…Similarly, a multicentric retrospective study from AIRO (Italian Association of Radiotherapy and Clinical Oncology) for patients with brain metastases from NSCLC reported that patients with the interval between SBRT and IO ≤ 7 days had a longer survival compared with the interval between SBRT and IO > 7 days. 413 This study data supports the delivery of SBRT and IO within a short time frame given that concurrent therapy is shown to be more effective without having an impact on toxicity. In conclusion, these data from clinical trials and retrospective studies indicate that concurrent iRT may be more effective than sequential one.…”
Section: Clinical Practicesupporting
confidence: 70%
“…In these stage IV patients, local response rates ranging from 74% to 89% and survival rates of 45 months have been observed [29] , [30] . Experiences that reported a significantly greater (but still acceptable, <14%) rate of brain radionecrosis for combination of immunotherapy (IT) and SRT with respect to SRT alone [31] are counter-balanced by as many which denied such a risk [32] , [33] , some of these with quite large population [33] . However, all of them agree that IT/SRT association improves survival outcomes.…”
Section: Introduction/rationalementioning
confidence: 99%
“…However, radiotherapy was a tendency factor with a better overall survival. S. Scoccianti et al found that in non-adenocarcinoma histology, for patients receiving immunotherapy and stereotactic radiotherapy, the performance status of was a vital factor affecting prognosis (23). Another study pointed out that radiotherapy was a self-reliant factor of good prognosis in patients with NSCLC treated with immune checkpoint inhibitors (27).…”
Section: Discussionmentioning
confidence: 99%